2008
DOI: 10.1523/jneurosci.4497-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Transient Receptor Potential Vanilloid 4, Integrin, and Src Tyrosine Kinase in Mechanical Hyperalgesia

Abstract: Although the transient receptor potential vanilloid 4 (TRPV4) has been implicated in the process of osmomechanical transduction, it appears to make little contribution to the normal somatosensory detection of mechanical stimuli. However, evidence suggests that it may play an important role in mechanical hyperalgesia. In the present study, we examined the common requirement for TRPV4 in mechanical hyperalgesia associated with diverse pain models and investigated whether the very close association observed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
170
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(184 citation statements)
references
References 71 publications
12
170
0
2
Order By: Relevance
“…By both genetic and pharmacological approaches, we showed that TRPA1 entirely mediates mechanical and cold hypersensitivity induced by oxaliplatin and cisplatin [146] in mice and rats. We confirmed [103] that TRPV4 mediates part of the mechanical hyperalgesia induced by paclitaxel [74], and we showed that TRPV4-resistant mechanical hyperalgesia was exclusively mediated by TRPA1 [103]. We also discovered that paclitaxel-induced cold allodynia was completely due to TRPA1 activation [103].…”
Section: Trpa1supporting
confidence: 67%
See 3 more Smart Citations
“…By both genetic and pharmacological approaches, we showed that TRPA1 entirely mediates mechanical and cold hypersensitivity induced by oxaliplatin and cisplatin [146] in mice and rats. We confirmed [103] that TRPV4 mediates part of the mechanical hyperalgesia induced by paclitaxel [74], and we showed that TRPV4-resistant mechanical hyperalgesia was exclusively mediated by TRPA1 [103]. We also discovered that paclitaxel-induced cold allodynia was completely due to TRPA1 activation [103].…”
Section: Trpa1supporting
confidence: 67%
“…Notwithstanding, recent evidence has emphasized a primary role for members of the TRP family, in particular TRPV1, TRPV4, TRPA1, and TRPM8, in the mechanical and thermal hypersensitivity evoked by chemotherapeutic agents in rodents [62,74,75].…”
Section: The Role Of Trp Channels In Chemothera-py-induced Peripheralmentioning
confidence: 99%
See 2 more Smart Citations
“…TRPV4 participation in osmo-and mechanotransduction (1, 2) contributes to important functions including cellular (3, 4) and systemic volume homeostasis (5, 6), arterial dilation (7,8), nociception (9), epithelial hydroelectrolyte transport (10, 11), bladder voiding (12), and ciliary beat frequency regulation (13)(14)(15). TRPV4 also responds to temperature (16,17), endogenous arachidonic acid (AA) metabolites (18), and phorbol esters including the inactive 4␣-phorbol 12,13-didecanoate (4␣PDD) (19,20) and participates in receptor-operated Ca 2ϩ entry (15), thus showing multiple modes of activation.TRPV4 channel activity can be sensitized by co-application of different stimuli (9,21,22) or participation of different cell signaling pathways (14), suggesting the presence of different regulatory sites. In this sense, several proteins have been proposed to modulate TRPV4 subcellular localization and/or function: microtubuleassociated protein 7 (23), calmodulin (CaM, (24)), with no lysine protein kinases (25), and PACSIN3 (26).…”
mentioning
confidence: 99%